Neutrophil to lymphocyte ratio predicts disease progression following intra-arterial therapy of hepatocellular carcinoma. Issue 5 (May 2017) - Taussig, Matthew D.; Irene Koran, Mary Ellen; Mouli, Samdeep K.; Ahmad, Asma; Geevarghese, Sunil; Baker, Jennifer C.; Lipnik, Andrew J.; Banovac, Fil; Brown, Daniel B.
Abstract: Background: Prospectively predicting response to intra-arterial therapy for hepatocellular carcinoma (HCC) is challenging. Neutrophil/lymphocyte ratio (NLR) is a serum biomarker that is associated with survival for multiple malignancies. It was hypothesized that increased NLR would be associated with early disease progression after intra-arterial therapy of HCC. Methods: The outcomes of 86 treatment-naïve patients who had chemoembolization or radioembolization of HCC between July 2013–July 2014 were reviewed. Pre-treatment laboratory tests and imaging were used to measure NLR, Child-Pugh (CP) score, tumor number and tumor size. High/low NLR groups were defined as >3 and <3 respectively. Follow-up imaging at two months with assessed response using modified response criteria in solid tumors (mRECIST). Results: NLR >3 was seen in 25/86 patients (range 3.0–21.6). NLR >3 patients had a significantly higher baseline CP score. Comorbidities were otherwise similar between groups as was tumor number/size. Disease control was significantly worse (p = 0.014) with NLR >3. Logistic regression for tumor response revealed NLR >3 as the best predictor of early progression (p < 0.0001). Discussion: NLR may be a serologic biomarker of early progressive disease after intra-arterial therapy of HCC. Future research should focus on outcomes by treatment type or potentially combining arterial therapies with ablation and/or targeted biologic agents.